2000
DOI: 10.1159/000054516
|View full text |Cite
|
Sign up to set email alerts
|

Galanin’s Functional Significance in the Regulation of the Neuroendocrine Reproductive Axis of the Monkey

Abstract: Galanin stimulates the neuroendocrine reproductive axis in the rat, but whether galanin acts similarly in primate species is unknown. To test the hypothesis that galanin acts within the hypothalamo-hypophyseal axis to stimulate luteinizing hormone (LH) and gonadotropin-releasing hormone (GnRH) secretion in the primate, galanin was administered either systemically or directly into the arcuate nucleus-median eminence of ovariectomized macaques (pigtailed or rhesus, respectively) that were maintained on estradiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
2
17
0
2
Order By: Relevance
“…For example, neuropeptide Y (NPY) is a potent stimulator of food intake but inhibits reproduction in male rats (Pierroz, Catzeflis, Aebi, Rivier, and Aubert, 1996;Sainsbury, Schwarzer, Couzens, Jenkins, Oakes, Ormandy, and Herzog, 2002). POMC also decreases food intake and stimulates endocrine reproductive physiology (Finn, Pau, Spies, Cunningham, Clifton, and Steiner, 2000;Kalra, Dube, Pu, Xu, Horvath, and Kalra, 1999;Thornton, Cheung, Clifton, and Steiner, 1997). Conversely, central injections of galanin-like peptide (GALP) decrease food intake and body weight (Krasnow, Fraley, Schuh, Baumgartner, Clifton, and Steiner, 2003;Seth, Stanley, Dhillo, Murphy, Ghatei, and Bloom, 2003), but stimulate sex behavior and LH secretion in male rats (Fraley, Thomas-Smith, Acohido, Steiner, and Clifton, 2004;Krasnow et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, neuropeptide Y (NPY) is a potent stimulator of food intake but inhibits reproduction in male rats (Pierroz, Catzeflis, Aebi, Rivier, and Aubert, 1996;Sainsbury, Schwarzer, Couzens, Jenkins, Oakes, Ormandy, and Herzog, 2002). POMC also decreases food intake and stimulates endocrine reproductive physiology (Finn, Pau, Spies, Cunningham, Clifton, and Steiner, 2000;Kalra, Dube, Pu, Xu, Horvath, and Kalra, 1999;Thornton, Cheung, Clifton, and Steiner, 1997). Conversely, central injections of galanin-like peptide (GALP) decrease food intake and body weight (Krasnow, Fraley, Schuh, Baumgartner, Clifton, and Steiner, 2003;Seth, Stanley, Dhillo, Murphy, Ghatei, and Bloom, 2003), but stimulate sex behavior and LH secretion in male rats (Fraley, Thomas-Smith, Acohido, Steiner, and Clifton, 2004;Krasnow et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Galanin is coexpressed with GnRH in the forebrain of the female rat and has been linked to the control of LH release in rodents and primates [8, 33]. Curiously, LH levels were not altered with respect to controls in either GALTG or GALKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Of galanin’s many postulated roles, its regulation of neuroendocrine processes has been among the most comprehensively studied. Galanin is coexpressed with gonadotropin-releasing hormone (GnRH) in several species, and it has been shown to induce LH release in both rodent and primate species [6, 7, 8]. Galanin is also coexpressed with growth hormone-releasing hormone in the hypothalamic arcuate nucleus, and infusions of galanin stimulate the release of growth hormone [9, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…It is almost certain that other neuropeptides will be shown to participate, too, including peptides yet to be discovered. For example, orexin, galanin, and galanin-like peptide all increase food intake and LH secretion (62,119,131,176,229), but a connection with nutritional infertility is yet to be determined. It has also been reported that melanocortins can increase circulating LH release (199) and sexual receptivity (44), but a role in nutritional infertility is doubtful (11,101,178).…”
Section: What About Other Neurotransmitter/neuropeptide Systems?mentioning
confidence: 99%